Refining the range of an importance index. (25th September 2014) - Mingo, Antonio; Newman, Jonathan
Summary An index measuring interaction importance (Iimp) was proposed in a paper published on 2010 by the Journal of Ecology. This index, now widely used by researchers, has been claimed to symmetrically range in the interval (−1, 1), with negative values for competition and positive values for facilitation. Here, the index properties are carefully analysed, and it is demonstrated that Iimp can never exceed the value of 0.5 in facilitation. Several years have passed since its publication, yet nobody has corrected the inexact index range, and several researchers continue to inaccurately refer to it. Overlooking this lack of symmetry could potentially lead to biased conclusions. Synthesis. I imp cannot be treated as a symmetric index for negative and positive interactions. This is only the last of several concerns discussed in literature: current approaches to measuring interaction importance still need to be debated and analysed in depth.